Crashes and Traffic Signal Violations Caused by Commercial Motorcycle Couriers - Dong Seok Shin; Jong Han Byun; Byung Yong Jeong (Elsevier, 2019)
Background: Motorcycles are one of the important members of commercial transportation because of the convenient use during congested traffic conditions and the ease of parking in narrow streets. This study investigates the characteristics of crashes and traffic signal violations caused by motorcycle couriers. Methods: From the national compensation data, this study analyzed the traffic crashes caused by 671 motorcycle couriers. Results: Among 671 injured couriers, 50.6% were aged less than 40 years, 49.2% run in a small business of <5 employees, and 47.2% had work experience of <6 months. Motorcycle crashes occurred mainly due to "rider overturned alone" (67.5%), in the daytime (73.5%), or on cloudy or clear days (77.2%). However, the violation rate caused by motorcycle couriers was high in couriers in a small business of <5 employees (13.9%), with work experience of <6 months (13.9%), on cloudy or clear days (12.4%), on an intersection (29.8%), in the type of "crash with a vehicle" (31.2%), or in a death accident (35.7%) Conclusion: The findings of this study can be used as a baseline in devising policies for preventing crashes of motorcycle couriers. Keywords: Courier safety, Motorcycle crash, Occupational injury, Rider ergonomics, Violation